Accounting for Output Drops in Latin America - Lama, Ruy (IMF Working Papers; Working Paper, 2009)
This paper evaluates what type of models can account for the recent episodes of output drops in Latin America. I develop an open economy version of the business cycle accounting methodology (Chari, Kehoe, and McGrattan, 2007) in which output fluctuations are decomposed into four sources: total factor productivity (TFP), a labor wedge, a capital wedge, and a bond wedge. The paper shows that the most promising models are the ones that induce fluctuations of TFP and the labor wedge. On the other hand, models of fnancial frictions that translate into a bond or capital wedge are not successful in explaining output drops in Latin America. The paper also discusses the implications of these results for policy analysis using alternative DSGE models.